2006
DOI: 10.1038/sj.tpj.6500387
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the pharmacogenetics of asthma treatment

Abstract: Asthma affects approximately 300 million individuals worldwide. Medications comprise a substantial portion of asthma expenditures. Despite the availability of three primary therapeutic classes of medications, there are a significant number of nonresponders to therapy. Available data, as well as previous pharmacogenetic studies, suggest that genetics may contribute as much as 60-80% to the interindividual variability in treatment response. In this methodologic review, after providing a broad overview of the ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 98 publications
(109 reference statements)
1
44
0
4
Order By: Relevance
“…However, degrees of responsiveness to b2-agonist plus ICS vary and approximately 60-80% of inter-individual variations may be due to genetic factors, and thus, several pharmacogenetic studies have been conducted to investigate the genetic basis of therapeutic response heterogeneity (8,9). Several clinical investigations have demonstrated that ADRB2 gene polymorphisms contribute to different bronchodilator responses to LABA (10)(11)(12)(13).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…However, degrees of responsiveness to b2-agonist plus ICS vary and approximately 60-80% of inter-individual variations may be due to genetic factors, and thus, several pharmacogenetic studies have been conducted to investigate the genetic basis of therapeutic response heterogeneity (8,9). Several clinical investigations have demonstrated that ADRB2 gene polymorphisms contribute to different bronchodilator responses to LABA (10)(11)(12)(13).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…To date, asthma pharmacogenetic studies in general (7), and response to inhaled bronchodilators in particular (8), have been based on one or more polymorphisms in a single gene. Recent studies from the Asthma Clinical Research Network, for instance, have reported adverse effects of regular albuterol treatment among patients with asthma who were homozygous for the 149 A allele (Arg16) of the ADRB2 gene (9,10).…”
Section: Abstract: Pharmacogenetics; Asthma; Bronchodilator Agentsmentioning
confidence: 99%
“…109 Therefore interpatient genetic variability is likely to be an important determinant of the effectiveness of treatment strategies in preventing progression. For example, a number of studies have examined the potential for desensitization immunotherapy to reduce the later occurrence of asthma.…”
Section: Genetic Variability and Response To Treatmentmentioning
confidence: 99%